Adverse (geno)toxic effects of bisphenol A and its analogues in hepatic 3D cell model. (January 2023) - Sendra, Marta; Štampar, Martina; Fras, Katarina; Novoa, Beatriz; Figueras, Antonio; Žegura, Bojana
Graphical abstract: Highlights: Cyto-/genotoxic effects of BPA and its analogues were assessed in in vitro 3D HepG2 cell model. BPFL and BPC proved to be the most cytotoxic analogues after short (24-h) and prolonged (96-h) exposure. BPA, BPAP, and BPAF induced DNA double-strand breaks. BPAF and BPC increased the percentage of p-H3-positive cells. All BPs induced DNA single-strand breaks, with BPAP being the most and BPA and BPC the least effective. Abstract: Bisphenol A (BPA) is one of the most widely used and versatile chemical compounds in polymer additives and epoxy resins for manufacturing a range of products for human applications. It is known as endocrine disruptor, however, there is growing evidence that it is genotoxic. Because of its adverse effects, the European Union has restricted its use to protect human health and the environment. As a result, the industry has begun developing BPA analogues, but there are not yet sufficient toxicity data to claim that they are safe. We investigated the adverse toxic effects of BPA and its analogues (BPS, BPAP, BPAF, BPFL, and BPC) with emphasis on their cytotoxic and genotoxic activities after short (24-h) and prolonged (96-h) exposure in in vitro hepatic three-dimensional cell model developed from HepG2 cells. The results showed that BPFL and BPC (formed by an additional ring system) were the most cytotoxic analogues that affected cell viability, spheroid surface area and morphology, cell proliferation, and apoptotic cell death. BPA, BPAP, and BPAF induced DNA double-strand break formation (γH2AX assay), whereas BPAF and BPC increased the percentage of p-H3-positive cells, indicating their aneugenic activity. All BPs induced DNA single-strand break formation (comet assay), with BPAP (≥0.1 μM) being the most effective and BPA and BPC the least effective (≥1 μM) under conditions applied. The results indicate that not all of the analogues studied are safer alternatives to BPA and thus more in-depth research is urgently needed to adequately evaluate the risks of BPA analogues and assess their safety for humans.